784
Chat with our AI personalities
The question is ambiguous: xa+1 * xa+1 = x2(a+1) or (xa + 1)(xa + 1) = x2a + 2xa + 1
It is a consequence of the isomorphism between powers of numbers under multiplication and their indices under addition. This leads to the definition of x-a as the [multiplicative] inverse of xa. Then xa * x-a = xa-a = x0 But since x-a is the inverse of xa, their product is 1. That is to say, x0 = 1.
x to the power a divided by x to the power b = x to the power (a - b), ie xa/xb = xa-b. When a = b, xa/xb = 1 and a - b = 0 so xa-b = x0. Rearranging gives x0 = 1. This is true for ALL non-zero values of x.
Any number raised to the power 0 is 1. This follow from the law of multiplications of power: xa * xb = xa+b Now, if you put b = 0, you get xa + x0 = xa+0 and since a+0 = a, the right hand side is xa. So you have xa * x0 = xa and using the property of the multiplicative identity, xa = 1.
0.75